The electronic behavior of zinc-finger protein binding sites in the context of the DNA extended ladder model - Oiwa, Nestor Norio; Cordeiro, Claudette E.; Heermann, Dieter W. (Arxiv, 2015)
The eukaryotic Cys2His2 zinc finger proteins bind to DNA ubiquitously at highly conserved domains, responsible for gene regulation and the spatial organization of DNA. To study and understand the zinc finger DNA-protein interaction, we use the extended ladder in the DNA model proposed by Zhu, Rasmussen, Balatsky & Bishop (2007) \cite{Zhu-2007}. Considering one single spinless electron in each nucleotide $π$-orbital along a double DNA chain (dDNA), we find a typical pattern for the {\color{black} bottom of the occupied molecular orbital (BOMO)}, highest occupied molecular orbital (HOMO) and lowest unoccupied orbital (LUMO) along the binding sites. We specifically looked at two members of zinc finger protein family: specificity protein 1 (SP1) and early grown response 1 transcription factors (EGR1). When the valence band is filled, we find electrons in the purines along the nucleotide sequence, compatible with the electric charges of the binding amino acids in SP1 and EGR1 zinc finger.
Gesehen am 02.08.2017